Show that:
![(\frac{1}{2} )^{4} + (\frac{1}{3}) ^{4} + (\frac{1}{6})^{2} \div (\frac{1}{2})^{2} + (\frac{1}{ 3})^{2} + (\frac{1}{6}) - \frac{1}{36} = \frac{1}{6} (\frac{1}{2} )^{4} + (\frac{1}{3}) ^{4} + (\frac{1}{6})^{2} \div (\frac{1}{2})^{2} + (\frac{1}{ 3})^{2} + (\frac{1}{6}) - \frac{1}{36} = \frac{1}{6}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B2%7D+%29%5E%7B4%7D++%2B++%28%5Cfrac%7B1%7D%7B3%7D%29+%5E%7B4%7D++%2B++%28%5Cfrac%7B1%7D%7B6%7D%29%5E%7B2%7D++%5Cdiv++%28%5Cfrac%7B1%7D%7B2%7D%29%5E%7B2%7D++%2B++%28%5Cfrac%7B1%7D%7B+3%7D%29%5E%7B2%7D++%2B++%28%5Cfrac%7B1%7D%7B6%7D%29+-++%5Cfrac%7B1%7D%7B36%7D++%3D++%5Cfrac%7B1%7D%7B6%7D+)
Answers
Correct Question :-
check weather (1/2)⁴ + (1/3)⁴ + (1/6)² ÷ (1/2)² + (1/3)² + (1/6) - (1/36) = (1/6) or not ?
Solution :-
Solving LHS Part ,
→ (1/2)⁴ + (1/3)⁴ + (1/6)² ÷ (1/2)² + (1/3)² + (1/6) - (1/36)
According to BODMAS RULE Lets First Solve Divide Part ,
→ (1/2)⁴ + (1/3)⁴ + (1/6)² ÷ (1/2)² + (1/3)² + (1/6) - (1/36)
→ (1/2)⁴ + (1/3)⁴ + [ (1/36) ÷ (1/4) ] + (1/3)² + (1/6) - (1/36)
→ (1/2)⁴ + (1/3)⁴ + [ (1/36) × (4/1) ] + (1/3)² + (1/6) - (1/36)
→ (1/2)⁴ + (1/3)⁴ + (1/9) + (1/3)² + (1/6) - (1/36)
→ (1/16) + (1/81) + (1/9) + (1/9) + (1/6) - (1/36)
→ (1/16) + [ (1/81) + (1/9) + (1/9) ] + [ (1/6) - (1/36) ]
Taking LCM ,
→ (1/16) + [ (1 + 9 + 9) / 81 ] + [ (6 - 1) / 36 ]
→ (1/16) + (19/81) + (5/36)
Taking LCM again Now,
→ (81 + 304 + 180) /1296
→ (565 / 1296 )
→ ≠ RHS.
So, we can conclude That, LHS is Not Equal to RHS.
CORRECT QUESTION :-
SOLUTION :-
LHS :-
RHS :-
Let us solve the LHS.
∴ So, we conclude that, LHS ≠ RHS.